The Crowd in Requirements Engineering: The Landscape and Challenges - Groen, Eduard C.; Seyff, Norbert; Ali, Raian; Dalpiaz, Fabiano; Doerr, Joerg; Guzman, Emitza; Hosseini, Mahmood; Marco, Jordi; Oriol, Marc; Perini, Anna; Stade, Melanie (IEEE software, 2017)
Crowd-based requirements engineering (CrowdRE) could significantly change RE. Performing RE activities such as elicitation with the crowd of stakeholders turns RE into a participatory effort, leads to more accurate requirements, and ultimately boosts software quality. Although any stakeholder in the crowd can contribute, CrowdRE emphasizes one stakeholder group whose role is often trivialized: users. CrowdRE empowers the management of requirements, such as their prioritization and segmentation, in a dynamic, evolved style through collecting and harnessing a continuous flow of user feedback and monitoring data on the usage context. To analyze the large amount of data obtained from the crowd, automated approaches are key. This article presents current research topics in CrowdRE; discusses the benefits, challenges, and lessons learned from projects and experiments; and assesses how to apply the methods and tools in industrial contexts. This article is part of a special issue on Crowdsourcing for Software Engineering.